MEN AND WOMEN HAVE SIMILARLY SHAPED CARPOMETACARPAL JOINT BONES - Schneider, M. T. Y. (J Biomech, 2015)
Characterizing the morphology of the carpometacarpal (CMC) joint bones and how they vary across the population is important for understanding the functional anatomy and pathology of the thumb. The purpose of this paper was to develop a statistical shape model of the trapezium and first metacarpal bones to characterize the size and shape of the whole bones across a cohort of 50. We used this shape model to investigate the effects of sex and age on the size and shape of the CMC joint bones and the articulating surface area of the CMC joint. We hypothesized that women have similar shape trapezium and first metacarpal bones compared to men, following scaling for overall size. We also hypothesized that age would be a significant predictor variable for CMC joint bone changes. CT image data and segmented point clouds of 50 CMC bones from healthy adult men and women were obtained from an ongoing study and used to generate two statistical shape models. Statistical analysis of the principal component weights of both models was performed to investigate morphological sex and age differences. We observed sex differences, but were unable to detect any age differences. Between men and women the only difference in morphology of the trapezia and first metacarpal bones was size. These findings confirm our first hypothesis, and suggest that the women have similarly shaped trapezium and first metacarpal bones compared to men. Furthermore, our results reject our second hypothesis, indicating that age is a poor predictor of CMC joint morphology.